2017
DOI: 10.1016/j.ejso.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The association between performance parameters of physical fitness and postoperative outcomes in patients undergoing colorectal surgery: An evaluation of care data

Abstract: There is an association between preoperative parameters and postoperative outcomes in patients with colorectal cancer scheduled for resection. Patients benefit from an optimal preoperative physical fitness level. Specific interventions can target this physical fitness level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
2
27
4
Order By: Relevance
“…This might be a possible explanation for the discrepancy between our results and the previously mentioned studies 10,24 . Nevertheless, a recent Dutch study among a similar population of CRC patients published results in line with our findings, as no significant association between pre-operative HGS as a single measurement and the occurrence of postoperative complications was found 6 . On the other hand, the same Dutch study demonstrated a significant association between an overall better pre-operative physical fitness, defined by a combination of physical tests, and a lower incidence of postoperative complications 6 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This might be a possible explanation for the discrepancy between our results and the previously mentioned studies 10,24 . Nevertheless, a recent Dutch study among a similar population of CRC patients published results in line with our findings, as no significant association between pre-operative HGS as a single measurement and the occurrence of postoperative complications was found 6 . On the other hand, the same Dutch study demonstrated a significant association between an overall better pre-operative physical fitness, defined by a combination of physical tests, and a lower incidence of postoperative complications 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, a recent Dutch study among a similar population of CRC patients published results in line with our findings, as no significant association between pre-operative HGS as a single measurement and the occurrence of postoperative complications was found 6 . On the other hand, the same Dutch study demonstrated a significant association between an overall better pre-operative physical fitness, defined by a combination of physical tests, and a lower incidence of postoperative complications 6 . The absence of an association between HGS as a single measurement and the incidence of postoperative complications is in line with the results of our study as well as results from other recent studies that found no association between a pre-operative HGS as a single functional performance measurement, and the occurrence of postoperative complications 26,27 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The TUG test measures the ability to rise from an arm chair (43 to 47 cm in height), walk a short distance (3 m), return to the chair, and sit down again, all as quickly as possible. 6 The TUG test is associated with time to recovery of physical functioning (odds ratio [OR] of 1.274; 95% CI of 0.975 to 1.664; P = .008) scored on the modified Iowa level of assistance scale (mILAS) in patients undergoing colorectal surgery. 7 During the 2MWT, patients have to walk as far as they can in 2 min over a length of 15 m with their customary walking aid, if applicable.…”
Section: Description Of the Examination Strategy Of The Physical Thermentioning
confidence: 99%
“…However, the impact on postoperative outcomes in elderly patients with CRC has never been quantitatively examined by using formal frailty assessment instrument(s) [7]. Also, the underlying mechanisms by which frailty confer a poorer prognosis need to be determined yet [8][9][10]. In this systematic review and meta-analysis, we aimed to summarize current evidence and quantitatively evaluate the effect of frailty on postoperative outcomes in geriatric patients receiving surgery for CRC.…”
Section: Introductionmentioning
confidence: 99%